Peningkatan Hasil Belajar Siswa Melalui Media Audio Visual dan Peer Teaching Method (PTM) dalam Pembelajaran Bahasa Indonesia Kelas 6 di SD N 3 Baturejo - Tiara ra maharani; Elisa Maesaroh; Eva Luthfi Fakhru Ahsani (Latifah Pres, 2022)
This research was structured with the aim of improving student learning outcomes using the peer teaching method or peer tutoring with audio-visual learning media in class VI students at SD N 3 Baturejo, Sukolilo, Pati for the 2022/2023 academic year. This type of research is classroom action research (PTK) and using research models Kemmis and Mc. Taggart, where the teacher as the executor of learning and the researcher as an observer, but in cycle I and cycle II the researcher teaches using predetermined methods and media to observe the increase or decrease in student learning outcomes. This research was conducted in November, the subject of this research was students of class VI SD N 3 Baturejo consisting of 16 students. The object of this research is to increase student learning outcomes with data collection techniques using observation and interviews. Data were analyzed descriptively and presented in the form of tables and bar charts. The results showed an increase in student learning outcomes, namely in the first cycle of 70.31%, then experienced an increase in the second cycle to 77.19%. This shows an increase of 6.88%. Thus the use of peer teaching learning methods in learning Indonesian can increase the learning activity of students in class VI at SD N 3 Baturejo. Keywords: Peer teaching methods; learning outcomes ; peer tutors; audio visual